Effectiveness and cost-effectiveness of human papillomavirus vaccination strategies among men who have sex with men in China: a modeling study - Li, Yuwei; Lin, Yi-Fan; Wu, Xinsheng; Zhou, Xinyi; Tian, Tian; Guo, Zhihui; Fu, Leiwen; Yang, Luoyao; Lu, Zhen; Fan, Song; Lu, Yong; Ke, Wujian; et al. (Frontiers in Immunology, 2023)
Introduction The health and economic benefits of human papillomavirus (HPV) vaccination targeted at men who have sex with men (MSM) in developing settings have been rarely assessed. This study aimed to evaluate the effectiveness and cost-effectiveness of different HPV vaccination strategies among MSM in China. Methods A Markov model was developed to simulate HPV transmission dynamics among a total of 30.73 million MSM in China. The corresponding natural history included 6 states: susceptible, infected with low-risk subtypes, high-risk subtypes, anogenital warts and anal cancer, and deaths from anal cancer. MSM were divided into three age groups with cut-off points of 27 and 45 years. Alternative vaccination strategies were built by allocating bivalent, quadrivalent, nine-valent, or no vaccine to each of the groups. We generated the prevented infections and deaths by vaccination compared with baseline (no vaccination) and calculated incremental cost-effectiveness ratios (ICERs) to determine the optimal strategy. Results The model showed that in 10 years, at baseline, the existing cases of anogenital warts would reach 5,464,225 (IQR, 4,685,708-6,174,175); that of anal cancer would reach 1,922.95 (1,716.56-2,119.93), resulting in 940.55 (732.27-1,141.87) deaths. Under 50% vaccination coverage among one age group, the prevented cases of anogenital warts were maximized with quadrivalent vaccines allocated to MSM aged 27-45 years; that of anal cancer were maximized when offering nine-valent vaccines to the same group. Under 50% vaccination coverage among all groups, the lowest ICER (34,098.09 USD/QALY, 31,146.54-37,062.88) was reached when only quadrivalent vaccines were provided. Based on this strategy, when the annual vaccination rate increased by 30%, the ICER (33,521.75 USD/QALY, 31,040.73-36,013.92) would fall below three times China’s per capita GDP. When the vaccine price decreased by 60%, the ICER was reduced to 7,344.44 USD/QALY (4,392.89-10,309.23), indicating good cost-effectiveness taking China’s per capita GDP as a threshold. Conclusions HPV vaccination can effectively reduce the prevalence and mortality of related diseases among MSM in China, especially quadrivalent vaccines for anogenital warts and nine-valent vaccines for anal cancer. MSM aged 27-45 years were the optimal group for vaccination. Annual vaccination and appropriate adjustment of vaccine price are necessary to further improve the cost-effectiveness.